Entre as cores dos vivos e as faces da morte: culturas jurídico-penais entre o positivo e o consuetudinário Oliveira, Minas Gerais, 1839-1890 - Leonam Maxney Carvalho (2018)
This research investigates the notions of justice in the daily life of the society of Oliveira, Minas Gerais, between 1840, year of foundation of the town, and 1890, when promulgating the Penal Code of the Republic. Under the Criminal Code of 1830 and based on criminal cases (homicides, suicides and infanticides) and inventories of the Forum of the homonymous city, the possibilities of interpreting these notions were analyzed as constituent parts of daily legal or customary cultures, that is, constructed based on life experiences, traditions and the history of individuals of African and Afro-Brazilian origin. Based on the study of the criminal laws of the time and on the historical context of the nineteenth century Brazil, forms of understanding about the history of the interior of Minas Gerais were proposed as an integral part of a larger social and cultural context: the Atlantic world. Thus, comparing historical-cultural aspects present both in the production of laws and in complex police and legal practice, among others, the society of Oliveira was portrayed in these documents, through values and behaviors related to conceptions of justice, honor, punishment , violence, revenge, and religion. In this way, the legal-penal cultures of this population were understood as heterogeneous and multifaceted, and could vary in time and space, depending on the dynamics of the historical contexts around the Atlantic and its interconnected transformations.